IMPLEMENTASI KEBIJAKAN ALOKASI DANA DESA DI WILAYAH KECAMATAN AIRMADDIDI KABUPATEN MINAHASA UTARA - Marjuanti, Eka (JPAP: Jurnal Penelitian Administrasi Publik, 2015)
The purpose of this study is to provide an overview of the implementation of the Village Fund Allocation in District Airmadidi North Minahasa Regency, as well as contributing factors and obstacles affecting the implementation and the strategy that should be done within the framework of the successful implementation of the policy but it also will provide recommendations to the local government in the management of Allocation Village fund. The method used in this research is qualitative descriptive method, where the main instrument in the study is the researchers themselves. Sources of data used is the source of primary data and secondary data relating to the circumstances of empirical implementation of the Policy. The results showed that the implementation of the policy of the Village Fund Allocation (ADD) in the district of Minahasa Utaraberjalan Airmadidi quite smoothly. However, if it is linked to the achievement of objectives, the implementation of the Village Fund Allocation (ADD) in the District of North Minahasa Regency Airmadidi not optimal. Some of the factors that affect the implementation of the Village Fund Allocation (ADD) in District Airmadidi North Minahasa Regency is communication, resource capabilities, attitudes executor, bureaucratic structure, and the size and environmental policy objectives. Keywords: Policy Implementation, Village Fund Allocation, Airmaddidi, North Minahasa regency